Diabetes Awareness Among Patient’s Attendant Visiting in Teaching Hospital of Eastern Nepal - Ghimire, Hridaya Bibhu; Parajuli, P; KC, Heera; Parajuli, SB (Birat Journal of Health Sciences, 2017)
Introduction Diabetes is a prevalent non-communicable disease. It has increasing global trend. In Nepal, the prevalence of diabetes is also increasing. Awareness is vital to revent and early diagnosis of diabetes. Objectives The objective of study was to assess the awareness of diabetes and its related factors. Methodology This was a hospital based cross sectional study. Total of 503 patient’s a